Estimulación de la Memoria en Adultos Mayores Indígenas de la Comunidad Casipamba del cantón Guaranda, provincia Bolívar, periodo diciembre 2018- abril 2019 - Toalombo Guanotaxi, María Inés (2019)
The objective of this study was to stimulate memory in older Indigenous people. It addresses a problem that has been little studied in the local context, for which purpose the socio-demographic and mental profile of the elderly Indigenous people of the community of Casipamba is initially considered. The study is framed in an applicative descriptive type. We worked with 32 indigenous elders who constitute the entire study population. The study variables were cognitive functions, especially memory; for which the MINI MENTAL STATE EXAMINATION (MMSE) assessment scale from Folstein was applied, and the Neuropsi neuropsychological evaluation test from F. Ostrosky-Solís, A. Ardila and M. Roosselli; For the establishment of sociodemographic characteristics, a questionnaire was developed. The stimulation of the memory was done with the Workbook: Memory problems, in 20 group sessions. The presentation of the results was done through the application of descriptive statistical techniques, and hypothesis testing through the application of Chi square. The main results found were 17 with severe deterioration, 3 with moderate deterioration in the experimental group, and in the control group we have 10 with severe deterioration, 1 with moderate deterioration, 1 with dementia. After applying the Mini Mental and Neuropsi Memory tests, the following results were obtained in the experimental group 12 with moderate deterioration, 8 with severe deterioration, in the control group 7 with moderate deterioration, 5 with severe deterioration, demonstrating that the experimental group improved by the stimulation and the control group improved only by keeping them active. Therefore, cognitive stimulation is necessary to improve the memory of indigenous older adults Key words: stimulation, memory, elderly, indigenous